Sara Lee : a tale of another turnaround - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
Sara Lee Corporation's acquisition binge in the 1980s and 1990s left the company with a portfolio of vastly different businesses operating independently of one another. It had experienced rapid top-line growth, but at the same time cash flows had declined. Sara Lee ignored both internal and external warning signs until a major transformation plan became necessary. This case examines the company's multiple turnaround attempts. The learning objective of the case is to analyze 'early stage' turnaround efforts by examining how the company found itself in decline, evaluating its attempts to improve its performance, and assessing the turnaround plan.